Applications of Biological Diversity Information Systems towards Conservation at Lawachara National Park in Bangladesh - Md. Rahimullah, Miah; Alexander Kiew, Sayok; Ahi, Sarok; Mohammad Belal, Uddin (Asian Business Consortium, 2016)
The study investigates a framework for Biological Diversity Information Systems (BDIS) with relevant rules and regulations that emphasize the need for interdisciplinary research collaborations at national, regional and global scales on nature conservation mechanisms at Lawachara National Park (LNP) in Bangladesh. To date, Bangladesh has no Integrated National Biodiversity Database with Clearing House Mechanisms. So, there is a lot of nature conserving problems faced on biodiversity management systems. The study integrates technological information from stakeholders like park manager, biological diversity specialists, network officers, ecological specialists, policy-makers, wildlife managers, academicians and relevant bodies. The study represents the uniqueness of the tools used to enhance conservation professionals on the national biodiversity strategic action plan through existing policies and technology, literature reviews, observations, interviews and reconnaissance findings. Approximately 64% of the respondents agreed for the development of Integrated Biological Diversity Information Systems (BDIS) for conserving nature at LNP. The study describes the essential information needed for comprehensive data exchange, data indexing, web-publication and reports on Convention on Biological Diversity with the help of Resources Information Management System. Finally, the study suggests future research trajectories using a new collaborative approach to drive the methodological agenda and recommends ways to further incorporate the information systems integrating next generations’ biodiversity conservation perspectives